Foodborne disease in Kenya: County-level cost estimates and the case for greater public investment - Hoffmann, Vivian; Baral, Siddhartha (International Food Policy Research Institute, 2020)
The right to safe food is enshrined in the Kenyan constitution. Through their jurisdiction over matters of agriculture – specifically crop and animal husbandry, abattoirs, and veterinary services – and health, including the licensing and control of undertakings that sell food to the public, county governments in Kenya have a critical role to play in meeting this obligation to their citizens.